Stable Redox-Cycling Nitroxide Tempol Inhibits NET Formation - Hosseinzadeh, Ava; Messer, Philipp K.; Urban, Constantin F. (Frontiers in Immunology, 2012)
To prevent the spread of pathogens neutrophils as the first line of defense are able to release Neutrophil Extracellular Traps (NETs), a recently discovered form of immune response. Reactive oxygen species (ROS) have been shown to be essential for many different induction routes of NET formation. Therefore, pharmacological inhibition of ROS generation has implications for research and medicine related to NETs. The application of diphenylene iodonium (DPI), an inhibitor of NADPH oxidase activity, is limited due to its toxicity to host cells as well as microbes. Therefore, we investigated the effect of 4-hydroxy-2,2,6,6-tetramethylpiperidine-1-oxyl (Tempol) a membrane-permeable radical scavenger on NET formation triggered by phorbol esters and Candida albicans. We quantified the amount of NETs with two complementary methods, using a microscopic analysis and an online fluorescence-based assay. In line with removal of ROS, Tempol reduced the amount of NET formation by neutrophils challenged with those stimuli significantly. Since Tempol efficiently blocks NET formation in vitro, it might be promising to test the effect of Tempol in experimental models of disorders in which NETs probably have hazardous effects.